IMPULSIVE BUYING BEHAVIOR PADA KONSUMEN ONLINE: Studi Fenomenologi Pada Pengguna Aplikasi Shopee - Sarah Shafira (2022)
Impulsive buying behavior is a phenomenon that occurs in the daily life of Indonesian people. Especially, adolescents and adults who live in urban areas, they have an impulsive tendency to reach the level of social standards and lifestyle. There are negative impacts of this behavior include, increased spending, feelings of regret related to financial problems, the desire to indulge in plans (non-financial), and feeling disappointed by buying excessive products. This study aims to find out the motives, experiences, and meanings of impulsive buying behavior on consumers online users of the Shopee application, using the theory of planned behavior. The method used is qualitative with a phenomenological approach. Sources of data in the form of primary data and secondary data. Researcher used three stages of data analysis according to Miles & Huberman, namely data reduction, data presentation, and conclusions drawing by data triangulation. This study also used NVivo 12 Plus software for the data analysis. The final result of this study shows that the motives of impulsive buying behavior on consumers online users of the Shopee application are based on the motives of seeking pleasure, filling boredom, fulfilling desires, fulfilling satisfaction and fulfilling needs. The experience of impulsive buying behavior on online consumers users of the Shopee application is pleasant and satisfying. The meaning of impulsive buying behavior is a spontaneous, sudden, unexpected, unintentional purchase to fulfill desires and satisfaction.